Effect Of Rice Husk Ash and Spent Mushroom Substrate Composte On The Growth And Yield Of Servo F1 Hybrid Tomatoes On Peat Soil Media - Silma Setyowati; Sigit Normagiat; Riko Prasetyo (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This study aims to determine the effect of rice husk ash and oyster mushroom baglog waste compost on the growth and production of servo tomato plants and obtain the best dose for application on peat soils.The research was conducted from January to May 2022. This study used the factorial randomized block design with two factors. First factor is rice husk ash with 4 levels: A0 (0 tons/ha), A1 (5 tons/ha), and A2 (7,5 tons/ha), A3 (10 tons/ha). The second factor is spent mushroom substrate composte with 4 levels: K0 (0 tons/ha), K1 (15 tons/ha), K2 (20 tons/ha), and K3 (25 tons/ha). This study consisted of 16 combinations of treatments that were repeated 3 times. The variables observed were plant height, number of leaves, fresh weight of planting, dry weight of planting, number of cropping fruits, weight of crop fruit, and fruit diameter. The data from the study were analyzed using a variety analysis (F test) with a level of 5%. The results showed that the combination of A2K1 treatment had an influence on the variables of plant height, fresh weight of plants, number of fruits planted, weight of crop fruit and diameter of fruits compared to A0K0.